PMO-251 A retrospective audit of colorectal cancer surveillance in inflammatory bowel disease in secondary care. (28th May 2012) - Burley, K; Arthurs, E; Gholkar, B; Williams, L; Lockett, M
Abstract : Introduction: Patients with colitis are at increased risk of colorectal cancer (CRC). Colonoscopic surveillance to detect dysplasia and early cancers has been advocated by the BSG since 2002. 1 Our aims were to assess whether patients with colitis in our patient cohort are receiving appropriate colonoscopic surveillance for CRC according to these guidelines, and to assess the impact of the updated 2010 BSG guidelines 2 on local endoscopy services. Methods: Patients with IBD were identified from secondary care coding databases and verified by paper records. A retrospective review of case notes was performed. Data on diagnoses, duration of symptoms, extent of disease and CRC surveillance was collected and analysed. Individualised recommendations for colonoscopic screening and surveillance were made according to the 2010 BSG guidelines. Results: 45 colitis patient records were reviewed; 20 CD: 25 UC, M:F 23:22. The average age was 59.4 (range 18.6–87); average duration of disease 18.6 (range 0–56). 35 (78%) had colitis extent requiring surveillance. 26 patients (58%) had symptom onset >10 years; 11 patients (42%) underwent screening colonoscopy at 8–10 years; 14 (54%) did not, one patient underwent colonoscopy but date of diagnosis was unclear. Nine patients (35%) underwent inconsistent surveillance, in six patients (23%) there was no record of a colonoscopy. Reasons for inconsistent or absent surveillance included non-attendance (2), patient declined (1) and unclear (11). 24 patients were eligible for repeat colonoscopy; 3 (13%) underwent this at the recommended interval; one patient was due in 2011; 11 (46%) underwent inconsistent surveillance; nine (38%) did not undergo any surveillance. Reasons for absent or inconsistent surveillance included non-attendance (2), lost to follow-up (1), patient declined (1), procedure unnecessary due to disease extent (1), patient undergoing surgery in the interval between colonoscopies (1) and unclear (14). Of 26 patients eligible for surveillance, 3 were excluded due to disease extent and intervening surgery. Of 23 remaining patients, the surveillance interval between colonoscopies would be increased in 12 patients (52%), unchanged in 6 (26%) and reduced in 3 (13%) with the introduction of the 2010 BSG guidelines. The impact was unclear in two patients (9%). Conclusion: Patients with colitis in our patient cohort at NBT are not receiving appropriate CRC surveillance according to BSG guidelines. These results emphasise the need for a robust coordinated surveillance programme. The 2010 guidelines have had the net effect of increasing the time interval between colonoscopies, which may lead to an overall reduction in endoscopy workload from surveillance cases. Competing interests: None declared. References: 1. Eaden JA, Mayberry JF. Gut 2002;51 (Suppl V):v10–12. 2. Cairns SR, et al. Guidelines. Gut 2010;59 :666–90.